Reviews of physiology, biochemistry and pharmacology 161 - Amara, Susan G.|q(Susan Gaye) 1954-.; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
Contents: F. Schweda and A. Kurtz: Regulation of Renin Release by Local and Systemic Factors M. Krauss and V. Haucke: Shaping Membranes for Endocytosis B.M. Jockusch and P.L. Graumann: The Long Journey: Actin on the Road to Pro- and Eukaryotic Cells B. Colsoul, R. Vennekens and B. Nilius: Transient Receptor Potential (TRP) Cation Channels in Pancreatic ß cells.
Electronic reproduction.
Keywords: Human physiology; Biochemistry; Pharmacology; Electronic books